Development of an ethogram for Predatory behaviour in dogs - STEVANIN, GIULIO (2022)
open Predatory Behaviour in domestic dog (Canis Familiaris) has been considered to stem from the Wolf (Canis Lupus) hunting sequence for a long time. Thus, any behavioural analysis of the hunting patterns performed on dogs has been studied in face of what was observed in its wild counterpart. Opposite to what was previously assumed according to their taxonomic classification and relatedness, further ecological and ethological studies performed on both the species had highlighted the differences in social structure between the two: pack composition and hierarchies, predisposition to tameness and therefore proximity to humans, which inevitably result in different hunting and foraging strategies. Furthermore, the ecological importance of the domestic dog must be considered, since following human migrations Canis Familiaris has become one of the most widespread animal species all over the world. Therefore, each interaction with a wide array of elements in the biosphere performed by the numerous dog populations all over each continent might produce significant additive effects in respect of the composition of the ecosystem in which they are present. In order to provide a more detailed and tailored description of this behaviour, observations featuring instances of predation in dogs have been collected from videoclips present in YouTube, Vimeo and other public sources. Such observations were then used to perform a behavioural analysis to identify the different phases that constitute the predatory behaviour sequence and to determine the criteria for their identification, in order to produce a functional ethogram. Since such an ethogram is not present in scientific literature about domestic dogs, its validation would provide a valuable standardized instrument that would allow to reach a better understanding of the behaviour of this species and may have a consistent transitional value towards other canine species, given the high availability of dogs and the ease of working with them. Predatory Behaviour in domestic ...